Sun drying of seedless and seeded grapes - Doymaz, Ibrahim (SPRINGER INDIA, 2012)
In this study, sun drying behaviour of seedless and seeded grapes was investigated. The drying study showed that the times taken for drying of seedless and seeded grapes of berry size of 1.72 cm and 2.20 cm thicknesses from the initial moisture contents of 78.2% and 79.5% (w.b.) to final moisture content of around 22% (w.b.) were 176 and 228 h in open sun drying, respectively. The drying data were fitted to 12 thin-layer drying models. The performance of these models were compared using the determination of coefficient (R-2), mean relative percent error (P), reduced chi-square (chi (2)) and root mean square error (RMSE) between the observed and predicted moisture ratios. The results showed that Midilli et al. model was found to satisfactorily describe the sun drying curves of seedless and seeded grapes. The effective moisture diffusivity values were estimated from Fick's diffusion model by 1.02 x 10(-11) and 1.66 x 10(-11) m(2)/s for seeded and seedless grapes.
Keywords: Sun drying; Seedless and seeded grapes; Thin-layer drying models; Non-linear regression; Effective moisture diffusivity; MOISTURE DIFFUSIVITY; SOLAR; KINETICS; PRETREATMENT; MICROWAVE; QUALITY; TEMPERATURE; PARAMETERS; MODELS; FRUITS; Food Science & Technology